Aplicación móvil de comercialización de productos en la farmacia Cruz Azul en la ciudad de Portoviejo - Vera Zambrano, Jorge Maron (2020)
This degree work aims to develop a web and mobile application to manage the commercialization of products from the Cruz Azul pharmacy in Portoviejo city, with the aim of promoting sales in a more comfortable way for the client, without the need of going to the establishment, where you can obtain the medicines or products that it’s offered; for the development of the software products, the Extreme Programming (XP) methodology was used, which has a framework divided into four phases; in the Planning phase, the user stories, used cases and iteration plan were prepared according to the requirements obtained through the survey that was carried out on the company manager; in the Design phase, the structures of the software modules, the REST APIs and the database were designed; in the Coding phase, the application modules were developed for which the programming languages php and TypeScript were used; in the Testing phase, unit and acceptance tests were carried out, in order to incorporate the latest modifications to the application if the case was required. Finally, all this process resulted in a mobile application whose data is managed by a web subsystem that allows control of the inventory that the client sees from the application, which was then proceeded with the delivery and commissioning.